Zooplankton diel vertical migration during Antarctic summer - Conroy, John A.; Steinberg, Deborah K.; Thibodeau, Patrica S.; Schofield, Oscar (W&M ScholarWorks, 2020)
Zooplankton diel vertical migration (DVM) during summer in the polar oceans is presumed to be dampened due to near continuous daylight. We analyzed zooplankton diel vertical distribution patterns in a wide range of taxa along the Western Antarctic Peninsula (WAP) to assess if DVM occurs, and if so, what environmental controls modulate DVM in the austral summer. Zooplankton were collected during January and February in paired day-night, depth-stratified tows through the mesopelagic zone along the WAP from 2009-2017, as well as in day and night epipelagic net tows from 1993-2017. The copepod Metridia gerlachei, salp Salpa thompsoni, pteropod Limacina helicina antarctica, and ostracods consistently conducted DVM between the mesopelagic and epipelagic zones. Migration distance for M. gerlachei and ostracods decreased as photoperiod increased from 17 to 22 h daylight. The copepods Calanoides acutus and Rhincalanus gigas, as well as euphausiids Thysanoessa macrura and Euphausia crystallorophias, conducted shallow (mostly within the epipelagic zone) DVMs into the upper 50 m at night. Rhincalanus gigas, T. macrura, and L. h. antarctica DVM behavior was modulated by chlorophyll a concentration, mixed layer depth, and depth of the subsurface chlorophyll a maximum, respectively. Carnivorous and detritivorous taxa – including the calanoid copepod Paraeuchaeta antarctica, ostracods, chaetognaths, and Tomopteris spp. polychaetes – as well as seasonally migrating copepods, were most abundant in the mesopelagic zone regardless of the diel cycle. Paraeuchaeta antarctica underwent reverse DVM within the top 100 m. The impacts of Antarctic zooplankton summer DVM and the resident mesopelagic assemblage on carbon export should be better quantified.